Recent trends in research on the health impacts of climate change in the Philippines (2018–2023): a scoping review - Clarissa De Guzman; Megan Lorenza Cabaero; Jude Raphael Lo; Jimmy Loro; Maria Vinna Crisostomo; Michelle Ylade; Kristal An Agrupis (Frontiers in Climate)
IntroductionClimate change poses significant health risks globally, particularly in vulnerable countries like the Philippines. This scoping review examines recent research trends (2018–2023) on the health impacts of climate change in the Philippines, building on previous national reviews and situating findings within global evidence.MethodsWe screened 8,346 articles from various databases and identified 69 studies meeting inclusion criteria. Using a framework-guided thematic synthesis, studies were categorized into 6 themes: vulnerability to disease and injury, direct health impacts of climate and weather, ecosystem-mediated impacts, health impacts mediated through human institutions, adaptation strategies, and co-benefits of mitigation measures.ResultsResults reveal a significant increase in climate-health research compared to a previous review (1980–2017), with notable growth in studies in mental health, gender-based vulnerabilities, and adaptation measures. However, research remains geographically concentrated in Luzon, highlighting regional disparities, and few studies utilized long-term climate-health datasets. Studies quantifying the health co-benefits of mitigation measures also remain limited.DiscussionThis review demonstrates significant progress while identifying persistent gaps. Future research should prioritize long-term surveillance, local adaptation evaluations and health-economic co-benefits studies to strengthen climate-health data integration, improve climate information services and develop equity-oriented, policy-relevant research agenda.